Characterization of copper sulfide leaching microbial consortia isolated from High-Andean acid mine drainage - Rodriguez-Venturo, Sofia (2023)
Bioleaching, using microbial consortia, is regarded as an eco-efficient and cost-effective alternative for the recovery of metals from low-grade ores. In this study, we conducted physiological and molecular characterization of psychrotolerant leaching microbial consortia (PLMC) isolated from acid mine drainage in four mining sites within the Pasco and Huarochirí provinces of Peru, situated at altitudes above 4200 meters. Six consortia adapted to a medium containing ferrous ions (9K medium) and a basal medium with 0.5% w/v CuS at 15°C were isolated. All consortia exhibited copper release. The PLMC with the most robust growth achieved a copper recovery of 12.47% within 30 days of evaluation. 16S rRNA gene sequencing analysis of the bacterial community revealed that the PLMCs were predominantly dominated by the genus Acidithiobacillus, followed by Acidiphilium. In conclusion, consortia suitable for copper biolixiviation in high-altitude mining contexts were successfully obtained.